Astaxanthin Induces Transcriptomic Responses Associated with Lifespan Extension in Caenorhabditis elegans - Feng Ding; Yan Zhao (MDPI AG, 2022)
Astaxanthin is a marine xanthophyll carotenoid which effectively prevents intracellular oxidative stress and has beneficial effects against various human diseases. It has been shown that astaxanthin protects Caenorhabditis elegans (C. elegans) from oxidative damages and extends the lifespan of C. elegans possibly by modulating genes involved in insulin/insulin-like growth factor (IGF) signaling (IIS) and the oxidoreductase system, although the exact mechanisms remain elusive. In this study, RNA sequencing analyses were employed to identify the differentially expressed genes in C. elegans in response to astaxanthin treatment. A total of 190 mRNAs and 6 microRNAs (miRNAs) were significantly changed by astaxanthin treatment in C. elegans. Gene ontology (GO) term and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses indicated that the mRNAs and miRNAs significantly altered by astaxanthin mainly function in innate immunity, lipid metabolism and stress responses, a significant portion of which are related to lifespan regulation in C. elegans. The study revealed novel mRNA and miRNA targets of astaxanthin, providing new insights for understanding the anti-aging mechanisms and the biological function of astaxanthin.